2016
DOI: 10.1186/s12966-016-0358-x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in moderate-to-vigorous physical activity among girls and overweight and obese schoolchildren during school- and out-of-school time

Abstract: BackgroundIncreasing physical activity (PA) during the school day and out-of-school time are critical strategies for preventing childhood obesity and improving overall health. The purpose of the present investigation was to examine schoolchildren’s volume and type of PA during school-time and out-of-school, compared to national recommendations and differences by sex and weight status.MethodsThis cross-sectional analysis included 517 3rd-5th grade schoolchildren from 13 New England elementary schools (October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 30 publications
8
63
0
1
Order By: Relevance
“…While our findings suggest that EOtC may be a cost-effective, supplementary strategy for creating a more active and varied school day, boys spent approximately double the amount of time in MVPA compared to girls in the EOtC group, suggesting that EOtC may contribute to the gap in levels of PA between sexes that is already well established in the literature [32–34]. This gap between sexes increases during the transition from childhood to adolescence as girls’ MVPA declines more, with onset at younger age and from a lower starting point at onset, compared to boys’ [35].…”
Section: Discussionmentioning
confidence: 53%
“…While our findings suggest that EOtC may be a cost-effective, supplementary strategy for creating a more active and varied school day, boys spent approximately double the amount of time in MVPA compared to girls in the EOtC group, suggesting that EOtC may contribute to the gap in levels of PA between sexes that is already well established in the literature [32–34]. This gap between sexes increases during the transition from childhood to adolescence as girls’ MVPA declines more, with onset at younger age and from a lower starting point at onset, compared to boys’ [35].…”
Section: Discussionmentioning
confidence: 53%
“…Children and adolescents are recommended to engage in at least 60 minutes of moderate‐to‐vigorous PA (MVPA) per day . However, more than half of children and adolescents worldwide do not meet this recommendation . Spain also has this problem, and it especially affects Spanish adolescent girls, among which only 26% are physically active …”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that youths should spend 50% of recess (ie, time periods of noncurricular activities in school) and physical education classes (PEC) total time in MVPA . In this context, previous studies have reported a compliance rate of less than 25% with the school hour PA recommendation even lower than the percentage of compliance for the MVPA during the whole day, and showed that less than 15% of students satisfied the MVPA recommendations during recess and PEC …”
Section: Introductionmentioning
confidence: 99%
“…Thus, parental support would be more impactful on internalizing problems for overweight/obese white American youth. Indeed, African American youth are more tolerant of a wider range of body sizes . The question remains whether African American youth and their families experience more stress‐related bullying and weight‐related bullying, specifically.…”
Section: Discussionmentioning
confidence: 99%